Cysteine‐Selective Phosphonamidate Electrophiles for Modular Protein Bioconjugations. Issue 34 (29th April 2019) - Kasper, Marc‐André; Glanz, Maria; Stengl, Andreas; Penkert, Martin; Klenk, Simon; Sauer, Tom; Schumacher, Dominik; Helma, Jonas; Krause, Eberhard; Cardoso, M. Cristina; Leonhardt, Heinrich; Hackenberger, Christian P. R.
Abstract: We describe a new technique in protein synthesis that extends the existing repertoire of methods for protein modification: A chemoselective reaction that induces reactivity for a subsequent bioconjugation. An azide‐modified building block reacts first with an ethynylphosphonite through a Staudinger‐phosphonite reaction (SPhR) to give an ethynylphosphonamidate. The resulting electron‐deficient triple bond subsequently undergoes a cysteine‐selective reaction with proteins or antibodies. We demonstrate that ethynylphosphonamidates display excellent cysteine‐selective reactivity combined with superior stability of the thiol adducts, when compared to classical maleimide linkages. This turns our technique into a versatile and powerful tool for the facile construction of stable functional protein conjugates. Abstract : Staudinger—Ready—Go ! Ethynylphosphonamidates can be chemoselectively incorporated into a given molecule through a Staudinger‐phosphonite reaction, and they react specifically with cysteine residues on proteins to give thiol adducts that are stable under physiological conditions. This enables the facile fusion of complex molecules to proteins.